Preparation, properties and biological applications of water soluble chitin oligosaccharides from marine organisms - Ahmed, A.B.A.; Taha, R.M.; Mohajer, S.; Elaagib, M.E.; Kim, S.K. (2012)
Chitin oligosaccharides (COSs) can be isolated from various natural resources, which have widely been used in biological active supplements (BAS) for the benefit of humankind. Several technological approaches for the preparation of COSs such as enzymatic, chemical, acid-catalysts hydrolysis, microwave radiation, membrane bioreactor methods have been developed and among them, membrane bioreactor, bioconversion and continuous mass production technologies are reported to be excellent. Compounds isolated from natural products have made a drastic impact on the pharmaceutical industry and especially, water-soluble chitin oligosaccharides have shown greater clinical activity, which have been demonstrated in various cell lines of disease significance. The activities of these COSs were being investigated in different patients, animals and even plants as a broad phase clinical trial program. In the present article, we have discussed the COSs preparation by different methods through comprehensive diffraction procedures along with the merits and demerits given in detail. In addition, a summary of recent work describing the synthesis and biological activities of water-soluble COSs has been presented here.